Dinamika Utang Pemerintah dan Kesinambungan Fiskal di Indonesia Periode 1980-2005: Suatu Uji Perbandingan Tiga Pendekatan - Ramadhan, Gaffari; Simanjuntak, Robert A. (UI Scholars Hub, 2007)
Economic crisis which happened several years ago has caused many impacts to Indonesia. One of these impacts is a huge amount of government debt. Particularly, the government debt whether from domestic or foreign is one of the instruments to finance government expenditure which can not befulfilled entirely by revenues from taxes. However, using the government debt to fund the government expenditure has consequences for the government to pay-back not only for the interest rate but also for the principal of debt which have maturity-date in the future. The purpose of this study is to analyze how far the development of the government debt dynamic from both domestic and foreign is correlated to fiscal sustainability. This study uses a case of Indonesia in period 1980-2005 which is divided into three periods: before crisis (/980-1997), crisis (1998-2000), and after crisis (2001-2005). In this study, we use Branson (1992) to analyze the government debt dynamic. In addition, we also use different approaches to have several comparisons in our analysis by Hamilton and Flavin (1986), Wilcox (1989), and Trehan and Walsh (1991). Besides that, we also conduct projection of the ratio of government revenue to GDP which is needed to support in decreasing of the ratio of government debt to GDP in the middle-term until 2010. In summary, this study shows that after the crisis, the dynamic movement of the government debt is decreasing continuously. Furthermore, the government debt and the primary deficit still stand on the sustainable path, or the right track. Equally important, in the middle-term, the ratio of government revenue to GDP is still needed to maintain in decreasing of the government debt from year to year. Generally, this study shows that fiscal condition in Indonesia after the crisis reflects sustainable and suitable to the assumption of Non-Ponzi Game.